CONTINUOUS PEDIOCIN PRODUCTION BY PEDIOCOCCUS ACIDILACTICI USING DAIRY WASTE - Mandal, Barnalii (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The production of pediocin by Pediococcus acidilactici has been conducted in continuous operation using dairy waste, namely whey. Methods: Whey supplemented with yeast extract was used as growth media of P. acidilactici. A series of batch fermentation have been conducted in whey with varying concentrations (0–40 g/L) of yeast extract. A continuous mode of fermentation was performed at the dilution rate of 0.05–0.25/h. The volumetric productivity of pediocin in continuous run has also been compared with batch process. A mathematical model has been developed to explain the reactor performance for pediocin production in both batch and continuous processes. Results: The highest specific pediocin production rate (36.8 AU mg/cell dry mass/h) and growth rate (0.41/h) were observed in batch runs using whey broth supplemented with 20 g/L yeast extract. Maximum cell growth and pediocin activity were obtained at 1.36 g/L and 2286 AU/mL in batch experiments. The highest pediocin productivity (514125 AU/h) was found in continuous mode for a dilution rate of 0.0625/h. The model was validated through well matching of simulated data with experimental ones. Conclusion: The study should be suitable for large-scale implementation of pediocin production.